Por uma prática pedagógica pautada no diálogo interepistêmico e na valorização das epistemologias indígenas - Feitosa, Lara Hanna Ribeiro (Universidade Federal do Tocantins, 2022)
The decolonial critical perspective addresses the power relations that involve the production and circulation of knowledge in the cultural or scientific dimension of colonialism. It questions the matrices that tend to classify and exclude a multiplicity of epistemologies, producing hierarchies between knowledge and sustaining a series of prejudices. In this perspective, the objective of this study is to describe the Ritual da Tora Grande practiced by the Apinaje indigenous people (Macro Jê) and to point out some contributions of this ritual, based on Law No. 11,645 / 2008, for a pedagogical practice in the non-indigenous school based on in inter-epistemic dialogue. For that, it was necessary to address the context of the creation of Law No. 11,645 / 2008; characterize the Ritual da Tora Grande, highlighting its main elements; and to point out how this indigenous ritual can contribute to a pedagogical practice that helps to deconstruct hierarchies between knowledge and prejudice. It is a qualitative research with bibliographic survey, which makes theoretical approaches with the critical Decolonial perspective. The data show that the Ritual da Tora Grande is an important source of knowledge about the Apinaje to be approached in the non-indigenous school, mainly because they make it possible and allow the discussion of the historical relationship of respect of this people with the environment. The elements that make up body paintings in this ritual are also rich sources of knowledge to be taught at school, because they help to deconstruct the idea that indigenous peoples are outspoken, that their cultures are backward, constituting a very rich historical and pictographic collection of culture Apinaje.